Clinical characteristics of patients with anti-EJ antisynthetase syndrome associated interstitial lung disease and literature review. (April 2020) - Liu, Yin; Liu, Xiaoqing; Xie, Miaomiao; Chen, Zhiyong; He, Jian; Wang, Zhengge; Dai, Jinghong; Cai, Hourong
Abstract: Aim: Interstitial lung disease (ILD) is an extra-muscular manifestation of antisynthetase syndrome (ASS). The aim of this study is to analyze the clinical characteristics of anti-EJ associated ILD in a large cohort of patients. Methods: Retrospective cohort study of patients with anti-EJ associated ILD. All available data of clinical and laboratory characteristics, pulmonary function tests, laboratory parameters, high resolution computed tomography (HRCT) and treatment were collected and analyzed from medical records. Results: We identified 51 subjects. Average age at diagnosis was 55.6 years. Thirty-two of 51 patients were female. Concurrent autoantibodies against Ro52 were seen in 92.2% patients studied. HRCT patterns were mainly non-specific interstitial pneumonia (NSIP). The predominant myositis subset was amyopathic dermatomyositis (ADM) (41.2%) followed by dermatomyositis and polymyositis. Thirty-four patients improved on corticosteroids alone or in combination with immunosuppressive drugs as treatment and ten patients were stabilized. However, eleven patients (21.6%) initially improved during 12.0 ± 4.4 months, then progressively recurred despite steroid treatment (mean prednisone dose 11.6 ± 3.5 mg). The recurrence group included a significantly higher proportion of patients with NSIP pattern ( p  < 0.05). In the literature review the most common manifestations of anti-EJ ASS were ILD (89.3%) and myositis (58.9%). Conclusion: ILD are common features of the anti-EJ ASS. Patients with anti-EJ ILD often had an onset of ILD with lower lung-predominant opacities and NSIP. Although the disease responded well to the initial combination therapy of corticosteroid and immunosuppressant, recurrence was frequent. NSIP pattern was significantly more frequent in the recurrence group. Highlights: ILD are common features of the anti-EJ ASS. HRCT patterns were mainly NSIP. Anti-EJ ILD patients responded well to the initial therapy of corticosteroid with/without immunosuppressants. Anti-EJ ILD recurrence was observed during oral corticosteroid tapering.